Upaya Meningkatkan Hasil Belajar PPKn Materi Karakteristik Daerah Dalam Kerangka NKRI Melalui Discovery Learning Model Snowball Throwing Pada Peserta Didik Kelas VII B SMP Negeri 2 Mungkid Tahun Pelajaran 2021/2022 - Budiyati, Sri (Faculty Of Education, 2022)
One of the problems in learning PPKn (Civics) is that the results of learning Civics on Regional Characteristics whithin the framework of the Unitary State Of the republic of Indonesia are not ideal,indicator of statement is seen from the results of daily assessments that most student have not reached the KKM standar. To overcome this problem, a Classroom Action Research (PTK) was conducted using the Discovery Learning method with the Snowball Throwing model. The purpose of this study is the improve the learning outcomes of civics on Regional Characteristics within the framework of the unitary state of the Republic of Indonesia,through the discovery learning model of the Snowball Throwing model in class VII B student of SMP Negeri 2 Mungkid in the 2021/2022 academoc year. The subject were 31 student, the research data sources, were obtained from qualitative data the from data from observations of theacher and student activities and quantitative data in the from of tst data students learning outcomes. The results of the fist cycle research obtained that 17 student, who completed individually, with classical compleceted 55% with an average value of 77. While in results of the research in cycle II increased with number of students who completed as many as 31 students with a 100% compleceted percentage with an average value of 94 based on the results of study. Learning using the discovery Learning method of the Snowball Throwing mode can improve the learning outcome of class VII B grade students of SMP Negeri 2 Mungkid school year 2021/2022.